Evaluation of clinical pharmacist interventions on drug-related problems in the gastroenterology ward - SANCAR, MESUT; BECEREN, AYFER (My University, 2022)
Integrating clinical pharmacists in a multidisciplinary patient care team improves the treatment process by identifying and resolving drug-related problems (DRPs). The aim of the study was to determine the effect of clinical pharmacist intervention for DRPs in the gastroenterology service. The first period of the study was conducted between 15.06.2018 and 15.02.2019. Eighty patients admitted to the gastroenterology ward, who used at least one medication, were included in \"the study group\". The clinical pharmacist participated in ward rounds and made interventions to solve identified DRPs. In the second period of the study, the control group consisted of 80 patients admitted to the same ward between 01.03.2019 and 06.06.2019. DRPs were determined only from the data obtained from the hospital system in the control group. DRPs were classified according to the European Pharmaceutical Care Network (PCNE V9.1). A total of 136 and 46 with an average of 1.7 and 0.57 DRPs per patient (p <= 0.01) were identified in the study and control groups, respectively. Of the DRPs in the study group, 59 were related to treatment effectiveness, while 61 were related to treatment safety. Likewise, 21 DRPs were related to treatment effectiveness in the control group, while 12 were related to treatment (p <= 0.01). 65% of the interventions were made at the physician level and 49% at the drug level. 97% (n=133) of the total interventions were accepted. The number of DRPs was significantly reduced in the control group within the time frame after the clinical pharmacist intervention period. In conclusion, clinical pharmacists\" importance in detecting and preventing DRPs in the gastroenterology ward has been demonstrated.
Keywords: Temel Eczacılık Bilimleri; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacology; General Pharmacology, Toxicology and Pharmaceutics; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Pharmacology (medical); Pharmacy; Drug Guides; Clinical pharmacist; drug-related problems; gastroenterology; medication review; MEDICATION-RELATED PROBLEMS; RISK-FACTORS; ERRORS; RECONCILIATION; EVENTS; Clinical pharmacist; drug-related problems; gastroenterology; medication review